Fit for America : Major John L. Griffith and the quest for Athletics and Fitness - Lindaman, Matthew (Book collections on Project MUSE., 2018)
Fit for America is at once an intellectual biography of Major John L. Griffith, one of the preeminent intercollegiate athletics administrators of the twentieth century, and an in-depth look at how athletics shaped national military preparedness in a time of war and anticommunist sentiment. Lindaman traces Griffith's forty-year career, one that spanned both world wars and included his appointment as the first Big Ten commissioner from 1922 until 1945. Griffith also served as NCAA president in the 1930s and later became the secretary-treasurer during World War II. Throughout his career, he worked tirelessly to advance the role and importance of collegiate sports on a regional and national level. In an era of heightened fears of communism, Griffith saw intercollegiate athletics as a way to prepare young men to become fit, disciplined military recruits. Griffith also founded his own publication, the Athletic Journal, in 1922 in which he published opinion pieces and solicited the opinions of other leading coaches and administrators nationwide. Through these pages, Lindaman explores not only Griffith's philosophy but also the emergence of a coaching and athletic administration network. Drawing on voluminous primary source material and the many writings Griffith left behind, Fit for America brings long-overdue attention to a figure who was instrumental in shaping the world of American intercollegiate sports. -- Provided by publisher.